Firm Characteristics, Earnings Management, Tax Amnesty, and Firm Value (study in Indonesia public listed companies) - Arie Pratama (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
This research provided two analyses: (1) whether the firm characteristics and earnings management practices might influence the amount of tax amnesty's assets presented in the financial statement; and (2) whether the amount of tax amnesty's assets influenced the firm value. There are 86 observations obtained from Indonesian public listed companies that participate in the tax amnesty program during 2016 – 2017. This research used multiple regression to conduct each analysis. The results showed that a company with a high level of earnings management discloses more tax amnesty's assets. The result also showed that the higher the tax amnesty's assets, the lower the firm value would be. These results showed that a company that conducting earnings management utilise tax amnesty as a haven for avoiding political costs, but on the other side, the tax amnesty disclosure regarded by an investor as an act of confessions of past tax sins. Moreover, these results might contribute to the new insight into tax practices in global business.